Digoreste : um jogo para aprendizagem de física ambiental na educação básica - Luiz, Acabias Marques (2018)
Digoreste is an application that supports the classes of the disciplines of Natural Sciences, in particular the Physics, dealing with the Transversal Theme "Environment". Students of Ensino Regular and Educação de Jovens e Adultos, for the most part, interact and always want to be part of the connected world. The devices they carry have the advantage of internet access and playback of audio, video, text and images, but they are also capable of running programs, such as games. Teaching in a traditional way, the physics classes are the ones that nd more di culty in the interdisciplinarity proposed by the Parâmetros Curriculares Nacionais. In the State of Mato Grosso, which has representation of three biomes in its territory and is the engine of national agribusiness, Environmental Education becomes urgent. In order to understand and study the possibilities, it is the objective of this study to develop a serious game with the concepts of Environmental Physics that is aligned with the Educação Básica curriculum, so that it can be used as a support tool for the classes of the Physics discipline. For this, we have analyzed the relations between the curriculum and environmental themes, as well as verifying how current information technology is used in the context of environmental education. It presents a game for mobile devices, an artifact that can serve as a means of intervention in school classes. One of the main points of the research is also the analysis of the impacts and consequences, in the teachers and the students, of the proposal described in the methodology.